Contrast in monsoon precipitation over oceanic region of north Bay of Bengal and east equatorial Indian Ocean. (5th February 2018) - Pokhrel, Samir; Hazra, Anupam; Saha, Subodh Kumar; Chaudhari, Hemantkumar S.; Metya, Abirlal; Ghude, Sachin D.; Konwar, Mahen
ABSTRACT: This study explores the possible causes of rainfall distribution over the two major oceanic raining regions of the north Bay of Bengal (nBoB) and the east equatorial Indian Ocean (eEIO). Despite 17% difference in vertically averaged humidity, there is almost 34% difference in mean rainfall over these two regions. The climatological seasonal [June–September (JJAS)] mean (standard deviation) rainfall over nBoB region is always higher (lower) than that over the eEIO region in all the independent data used. The eEIO region has a much larger percentage of low stratiform and convective rainfall (<5 mm day −1 ) distribution as compared to nBoB, which is totally opposite in case of moderate stratiform and convective rainfall (>5 mm day −1 ) distribution. This is further substantiated by a much lower values of outgoing long‐wave radiation (OLR) in nBoB (<200 W m −2 ) as compared to the eEIO (217 W m −2 ) region. Mean Hadley circulation along with relative vorticity/divergence profile supports more intense (gentle) updrafts over nBoB (eEIO) region. Latent heat (LH) is almost three times at the upper level (∼8 km) in case of nBoB as compared to eEIO; however, at the lower level (∼3 km) LH is marginally higher over eEIO region. Microphysical variables, namely cloud ice optical thickness and cloud ice water path, are in much larger quantities over nBoB as compared to eEIO. Furthermore, the cold (warm) rain processes dominate among other microphysical processes over nBoB (eEIO) region. Thus, the interplay among large‐scale dynamics, thermodynamics and microphysics is very crucial in the formation of deep clouds and convective rain over the nBoB region and similarly shallow clouds and stratiform rain over the eEIO region. This study will be very useful to guide present‐day coupled models for proper representation of different rain components over the nBoB and eEIO region. Abstract : Schematic of different types of cloud and their associated processes over the (a) nBoB region and (b) eEIO region.